Company law in Ukraine: recent regulatory developments - Khort, Yu. V.; Хорт, Ю. В.; Хорт, Ю. В. (Одеса : Гельветика, 2018)
This article defines the main trends of the current renewed company legislation development, as well as, the extent to which the Ukrainian company law reform is related to the similar processes in the EU. The author analyzes the key aspects of the recently adopted changes in regulation of corporate contracts and limited liability companies as well as formation of the legal basis for the squeeze-out and sell-out transactions.

Корпоративне право в Україні: останні законодавчі новації. Стаття визначає головні тенденції розвитку чинного корпоративного законодавства України, а також надає оцінку його відповідності подібним процесам, що відбуваються в ЄС. Автором аналізуються ключові аспекти нещодавно прийнятих змін щодо регулювання корпоративних договорів, товариств з обмеженою відповідальністю, а також формування законодавчої основи для squeeze-out та sell-out.

Корпоративное право в Украине: последние законодательные новации. Статья определяет основные тенденции развития действующего корпоративного законодательства Украины, а также проводит оценку его соответствия подобным процессам, происходящим в ЕС. Автором анализируются ключевые аспекты недавно принятых изменений по регулированию корпоративных договоров, обществ с ограниченной ответственностью, а также формированию законодательной основы для squeeze-out и sell-out.
Khort Yu. V. Company law in Ukraine: recent regulatory developments / Yu. V. Khort // Актуальні проблеми держави і права : зб. наук. пр. Вип. 80 / редкол.: В. В. Завальнюк (голов. ред.) та ін. – Одеса : Гельветика, 2018. – С.187-201.
Keywords: joint-stock companies; limited liability companies; corporate contract; squeeze-out and sellout transactions; акціонерні товариства; товариства з обмеженою відповідальністю; корпоративний договір; обов’язковий викуп акцій; акционерные общества; общества с ограниченной ответственностью; корпоративный договор; обязательный выкуп акций